2011
DOI: 10.1111/j.1365-2966.2011.19498.x
|View full text |Cite
|
Sign up to set email alerts
|

Luminosities of recycled radio pulsars in globular clusters

Abstract: Using Monte Carlo simulations, we model the luminosity distribution of recycled pulsars in globular clusters as the brighter, observable part of an intrinsic distribution and find that the observed luminosities can be reproduced using either log-normal or power-law distributions as the underlying luminosity function. For both distributions, a wide range of model parameters provide an acceptable match to the observed sample, with the log-normal function providing statistically better agreement in general than t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
105
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 66 publications
(125 citation statements)
references
References 48 publications
20
105
0
Order By: Relevance
“…Similar results were found by Ridley & Lorimer (2010). The log-normal form of the luminosity distribution has subsequently been adopted as a starting point by a number of other studies (e.g., Boyles et al 2011;Bagchi et al 2011 andChennamangalam et al 2012; see also these proceedings). † For example, the psrpop software package at http://psrpop.phys.wvu.edu has modules to carry out both the snapshot and evolution approaches Galactic Millisecond Pulsars 239…”
Section: Overiew Of Modeling Approachessupporting
confidence: 71%
“…Similar results were found by Ridley & Lorimer (2010). The log-normal form of the luminosity distribution has subsequently been adopted as a starting point by a number of other studies (e.g., Boyles et al 2011;Bagchi et al 2011 andChennamangalam et al 2012; see also these proceedings). † For example, the psrpop software package at http://psrpop.phys.wvu.edu has modules to carry out both the snapshot and evolution approaches Galactic Millisecond Pulsars 239…”
Section: Overiew Of Modeling Approachessupporting
confidence: 71%
“…Globular clusters (GCs) are extraordinary factories of recycled pulsars; over the last 30 years, 146 pulsars have been discovered in Galactic GCs, with several thousands more still to be discovered (Bagchi et al 2011;Hessels et al 2015).This pulsar population is completely different from the Galactic population, with a very high fraction of pulsars with rotational periods of a few milliseconds (MSPs). One reason this happens is because GCs are very old stellar systems, so most "normal" pulsars in them have long faded into inactive neutron stars (NSs).…”
Section: Pulsars In Globular Clustersmentioning
confidence: 99%
“…Hessels et al (2007) also found that the luminosity distribution of globular cluster pulsars can be described by a power-law distribution, which is similar to what is proposed by Cordes & Chernoff (1997) based on 22 millisecond pulsars (Ps < 20 ms) found in the Galactic disc. Recently, Bagchi et al (2011) analysed about a hundred recycled pulsars found in globular clusters and fit the observed pulsar luminosity distribution with powerlaw and lognormal distributions. They concluded that a lognormal distribution is a slightly better fit to the observed luminosity distribution based on the χ 2 and KolmogorovSmirnov (K-S) statistics, although both power-law and lognormal distributions are, in general, consistent with the observation.…”
Section: Pulsar Luminosity Distributionmentioning
confidence: 99%